2007
DOI: 10.1073/pnas.0708440104
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical inhibition in a mouse model of familial childhood absence epilepsy

Abstract: Mutations in the GABAA receptor ␥2 subunit are associated with childhood absence epilepsy and febrile seizures. To understand better the molecular basis of absence epilepsy in man, we developed a mouse model harboring a ␥2 subunit point mutation (R43Q) found in a large Australian family. Mice heterozygous for the mutation demonstrated behavioral arrest associated with 6-to 7-Hz spike-and-wave discharges, which are blocked by ethosuximide, a first-line treatment for absence epilepsy in man. Seizures in the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
230
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(254 citation statements)
references
References 57 publications
24
230
0
Order By: Relevance
“…SWDs are generalized over wide cortical areas, requiring a massive synchronization of the thalamo-cortico-thalamic loop. Some studies proposed a leading role of the cortex in the generation of SWDs (10)(11)(12). In one such study using GAERS, a genetic rat model of absence seizures, infusion of ethosuximide into the cortex produced an immediate cessation of SWDs (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWDs are generalized over wide cortical areas, requiring a massive synchronization of the thalamo-cortico-thalamic loop. Some studies proposed a leading role of the cortex in the generation of SWDs (10)(11)(12). In one such study using GAERS, a genetic rat model of absence seizures, infusion of ethosuximide into the cortex produced an immediate cessation of SWDs (13).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal hypersynchronized oscillatory activities in the thalamocortical network, consisting of feedforward and feedback connections between the cortex and the thalamus, have been implicated as an underlying mechanism for the generation of SWDs (5)(6)(7)(8)(9). Some studies using rat models of absence seizures have suggested that the cortex plays a leading role in the generation of SWDs (10)(11)(12)(13). Other studies support the hypothesis that massive thalamocortical synchronization is driven from recurrent oscillatory activities in the network between reticular thalamic nucleus (nRT) and thalamocortical (TC) relay nucleus (3,8,9,14,15).…”
mentioning
confidence: 99%
“…Disrupted GABA A R trafficking contributes to altered information processing in pathological conditions such as epilepsy and ischemia, in which acute receptor surface downmodulation and loss of synaptic GABA A Rs leads to compromised neuronal inhibition and altered excitability states, but the underlying mechanisms remain unclear (Mielke and Wang, 2005;Naylor et al, 2005;Tan et al, 2007;). Indeed, although both clathrin-dependent and -independent (e.g., caveolar-dependent) pathways for GABA A R endocytosis have been described (Kittler et al, 2000;Bradley et al, 2008), the specific contribution of AP2-dependent pathways for synaptic receptor loss in epilepsy or ischemia remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They include autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) [7][8][9], benign familial neonatal convulsion (BFNC) [10,11], childhood absence epilepsy (CAE) [12,13], severe myoclonic epilepsy in infancy (SMEI) [14] and febrile seizures (FS) [15]. However, their phenotypic features have not been determined fully.…”
Section: Introductionmentioning
confidence: 99%